Application of the dynamic cone penetrometer test for determining the geotechnical characteristics of marl soils treated by lime. Issue 9 (September 2021) - Vakili, Amir Hossein; Salimi, Mahdi; Shamsi, Mohammad
Abstract: Quantitative estimation of mechanical characteristics of soils and determination of their behavior using in-situ experiments have always been one of the main concerns of geotechnical engineers. So far, various methods have been introduced to achieve this goal, among which the Dynamic Cone Penetrometer (DCP) test has become more popular as one of the most accurate and efficient methods. Therefore, in this study, an attempt was made to examine the correlation between different soil parameters by performing DCP test along with a series of conventional tests including Unconfined Compressive Strength (UCS) and California Bearing Ratio (CBR) tests on marl soil samples containing 2, 5, 8% lime at 1, 7 and 15 curing days. Furthermore, since the subgrade reaction coefficient (Ks ) is needed in the design of pavements and their underlying materials, Plate Load Test (PLT) was performed to determine Ks . The results showed that the addition of lime up to 5% increased UCS, CBR and Ks and decreased dynamic penetrometer index (DPI) of marl soil samples. Further addition of lime had a negative effect on the mechanical characteristics of the samples. Moreover, using the equations obtained from the correlations in this study, strength characteristics and subgrade reaction coefficient of the stabilized marl soil can be estimated by knowing the DPI of the samples. The results of this study showed that the use of the DCP test as a cheap and easy-to-use method can provide a comprehensive view of soil behavior in civil engineering projects with an acceptable coefficient of determination to geotechnical engineers. Abstract : Marl soil; Lime; DCP; CBR; PLT.